The Effect Of Corporate Social Responsibility, Profitability And Company Growth On Company Value: Case Study Of An Agricultural Company Listed On The Indonesian Stock Exchange In 2020-2022 - Zein Maula Naufiana Al-Haq; Yuliati Yuliati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The rapid business development in Indonesia, marked by the number of new companies listed on the IDX, causes more competitive competition. This means the company must be able to make investors interested in investing by increasing the company's value. A small company value indicates a need for more investor interest in the company. One of the industries that have this problem is agricultural industry companies on the IDX. This study aims to determine the effect of CSR, Profitability, and Company Growth on Company Value in agricultural companies listed on the IDX in 2020-2022. Data was obtained from financial reports and sustainability reports of agricultural companies registered on the IDX during 2020-2022 using a purposive sampling technique. The analysis used is multiple linear regression analysis. (1) CSR has a negative effect on company value; (2) Profitability has no influence on company value; (3) Company growth has a positive effect on company value; (4) Company value can be influenced simultaneously by CSR, Profitability, and Company Growth.